Evaluation of morin and carvacrol loaded-nanoparticles on oral polymicrobial biofilm control - Sales, Luciana Solera [UNESP] (2025)
This study aimed to develop and characterize sodium alginate (SA)/chitosan (CS) based nanoparticles (NPs), with or without morin or carvacrol, and to evaluate the antimicrobial and antibiofilm activity against polymicrobial oral biofilms. Three different NPs (0.15:1; 0.3:1; 0.5:1 CS:SA) whether or not containing morin or carvacrol were developed and characterized by particle size, zeta potential, scanning electron microscope (SEM), encapsulation efficiency, and in vitro drug release. NPs antibiofilm and antimicrobial activity were evaluated using polymicrobial oral biofilms by means of quantifying the biomass, assessment of viable microorganisms (CFU/mL), and acidogenicity of the biofilm by pH readings. The NPs presented nanometric size (<500 nm), with spherical shape and smooth surface. Encapsulation efficiency of the samples containing morin ranged from 46.17 to 55.15% and for carvacrol from 55.30 to 90.15%. Total release of carvacrol and morin occurred within 15 min. The NPs significantly reduced biofilm biomass and microbial viability compared to the control. However, did not significantly increase the biofilm pH. The NPs were effectively synthesized and showed antimicrobial and antibiofilm effect against oral biofilm and the addition of natural substances morin or carvacrol increased this effect. Combination of chitosan and sodium alginate and addition of morin or carvacrol in NPs can be a promising strategy for oral use, fighting biofilm and consequently biofilm dependent diseases.